Evaluation of canal cleanliness and tubular penetration of root canal sealers in extracted primary second molars: a SEM study - Çiğdem Güler; Mehmet Güler; Taşkın Gürbüz; Yücel Yılmaz (Cumhuriyet University, 2013)
Objectives: To evaluate canal surface changes and the remaining debris/smear after canal preparation, and the subsequent penetration of root canal sealers into dentinal tubules in extracted primary second molars, using scanning electron microscopy (SEM). Materials and Methods: The widest roots of 120 recently extracted human primary second molars were used. The roots were randomly distributed into four groups, according to instrumentation techniques [conventional stainless-steel hand files / nickel-titanium (Ni-Ti) rotary files] and irrigation solutions [0.5% sodium hypochlorite (NaOCl) and 0.9% saline solution/0.4% chlorhexidine gluconate (CHX)] employed. Surface change, the debris/smear layer remaining after instrumentation/irrigation, and the tubular penetration of root canal sealers [zinc oxide and eugenol (ZOE)/Apexit Plus (AP)] were evaluated using SEM. All data were analyzed statistically using the Kruskal-Wallis and Mann-Whitney U tests. Results: No significant difference was found between the surface changes and debris/smear layer scores based on root canal preparation technique and irrigant solution (P>0.05). ZOE cement was unable to enter dentinal tubules, while AP-based calcium hydroxide was able to gain limited entry to the tubules of some roots, but not others. Conclusions: No differences in canal cleanliness were noted among the instrumentation and irrigant protocols evaluated. AP was found in this SEM study to penetrate the dentinal tubules of prepared primary molar root canals more effectively than ZOE; though, penetration with AP was not noted in every root canal.